Prognosis of pregnant women with epilepsy and their neonates: a case series study - Nagasaki, Hiraku; Nakamoto, Masaya; Hironaka, Kouhei; Ooshiro, Miya; Hiyane, Masato; Murata, Momoko; Uesato, Tadakazu; Inamine, Morihiko; Masamoto, Hitoshi (FUKUSHIMA JOURNAL OF MEDICAL SCIENCE, 2025)
Objectives:To explore the outcomes of pregnant women with epilepsy and their neonates, including the incidence of neonatal withdrawal syndrome.Methods:In total, 26 pregnancies in 20 mothers with epilepsy were retrospectively examined for the presence of complications before and during pregnancy, number of antiseizure medications taken, gestational weeks at delivery, mode of delivery, number of seizure episodes during pregnancy and postpartum, neonatal birth weight, Apgar score, pH of the umbilical cord arterial blood, neonatal abnormalities, and neonatal withdrawal syndrome.Results:Overall, 25 of the 26 pregnancies resulted in live births, with 4 cases undergoing premature deliveries.　Ten cases underwent cesarean section, with only one case undergoing cesarean section due to the fear of experiencing seizure during vaginal delivery.　During pregnancy, two cases experienced one seizure episode.　The rate of small for gestational age was 8.0%, and three neonates had congenital abnormalities.　Withdrawal symptoms were observed in 75% of the neonates, but none of them obtained ≥8 points in the withdrawal checklist, the threshold for pharmacotherapy.Conclusions:For women with epilepsy who receive medical management and establish good control prior to pregnancy, child birth may be relatively safe, with a low rate of neonatal withdrawal syndrome requiring pharmacotherapy.